CLASSIFICATION OF FACIAL EXPRESSIONS (THE RELATIONSHIP BETWEEN INNATIVE AND ACQUIRED FACIAL EXPRESSIONS) (Universal International Scientific Journal, 2026)
This article analyzes research on nonverbal communication, aiming to determinewhether nonverbal behaviors are determined by innate human patterns or are primarily shaped bycultural experience. In the 20th century, the prevailing approach was to view nonverbal communicationas entirely culturally dependent, and to explain observed cultural differences by specific notions of spaceand time
Keywords: nonverbal communication; innate facial expressions; emotions